In-vitro Anti-arthritic Evaluation of Gugguluthiktam kashayam & Simhanada guggulu by Protein Denaturation & Proteinase Inhibitory Method - Ratnaprava Mishra , Sreelekshmi G.U. (International Journal of Advanced Science and Technology, 2020)
AIM-The chief aim of the present investigation is to study In-vitro Anti-arthritic Evaluation of Gugguluthiktam kashayam & Simhanada guggulu by Protein Denaturation & Proteinase Inhibitory Method. MATERIAL & METHODS- Gugguluthikthakam Kashayam was prepared by soaking one part of coarse kashaya powder with 16 parts water, boiled till its volume reduced to 1/8th which was filtered and used. For Simhanada guggulu, take all the ingredients of the pharmacopoeial quality. Wash, dry and powder the ingredients Haritaki, Bibhitaka, and Amalaki of the formulation composition separately and pass through sieve number 40. Soak the coarse powder of ingredients Haritaki, Bibhitaka, and Amalaki in 4 times of potable water for 12 hours. The dried powder of both selected drugs i.e. Gugguluthiktam kashaya & Simhanada guggulu were suspended in distilled water. The following procedure was followed for evaluating the percent of inhibition of protein denaturation. The dried powder of both selected drugs i.e. Gugguluthiktam kashaya & Simhanada guggulu were suspended in distilled water and the following procedure was followed for evaluating the Proteinase Inhibitory Activity. RESULTS- The both drugs were analyzed by protein denaturation method at concentration range of 100-500 µg/ml. Diclofenac sodium showed 74.76 percentage inhibition at the concentration of 100 µg/ml while Simhanada guggulu and Gugguluthiktam kashaya showed 71.51and 64.37 at the concentration of 500 µg/ml. The both drugs were analyzed by Proteinase inhibitory activity at concentration range of 100-500 µg/ml. Diclofenac Sodium was used as a Standard drug or reference drug for the comparison. Diclofenac Sodium was used in a concentration of 20, 40, 60, 80 & 100 µg/ml. The standard drug showed maximum percentage of inhibition as compared to test drug. CONCLUSION - In conclusion, it can be stated that the Simhanada guggulu and Gugguluthiktam kashaya have beneficial effects against protein denaturation and proteinase inhibition.